Modified liquid crystal polymer composition, copper-clad plate and preparation method of copper-clad plate
By adding modification additives to the liquid crystal polymer resin, the bonding force between the liquid crystal polymer film and copper foil is improved, and the problem of insufficient performance of existing flexible copper clad plates in 5G high-frequency communication is solved, and efficient signal transmission is achieved.
Patent Information
- Application Number
- CN202411989567.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing flexible copper clad plates are insufficient in 5G high-frequency communication, especially the dielectric properties, water absorption and thermal expansion coefficient of polyimide (PI) flexible copper clad plates cannot meet the requirements of high-frequency signal transmission.
By adding a modified additive to the liquid crystal polymer resin, the wetting and bonding force between the modified liquid crystal polymer film and the copper foil is improved, and a modified liquid crystal polymer composition is prepared to form a flexibility with excellent peel strength. Copper clad plate.
It realizes high bonding force between the modified liquid crystal polymer film and copper foil, improves the peel strength of the flexible copper clad plate, and is suitable for 5G high-frequency signal transmission.
Smart Images

Figure CN119391202A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid crystal polymers, and in particular relates to a modified liquid crystal polymer composition, a copper clad laminate and a preparation method thereof. Background Art
[0002] With the rapid development of 5G technology, the application demand for high frequency and high speed has put forward higher requirements on the transmission loss of materials, prompting the accelerated development of high frequency application technology. At the same time, the expansion and enhancement of application product functions, such as photography, Bluetooth, Wi-Fi, 5G Internet access, fingerprint recognition and wireless charging devices, more and more functions need to be integrated together, making the design of high-speed and high-frequency substrate materials responsible for signal transmission functions, that is, flexible copper clad laminates, tend to be high-precision and high-density, and the demand for flexible copper clad laminates is also increasing day by day.
[0003] Flexible copper clad laminate (FCCL) is a polymer composite substrate covered with single-layer or multi-layer wiring. At present, the medium and high frequency FCCL widely used in the industry is mainly polyimide (PI) flexible copper clad laminate (PI-FCCL), but PI has a high dielectric constant (dielectric constant ≥ 3.4), which cannot meet the requirements of 5G high-frequency communication for dielectric dielectric properties (dielectric constant < 3.0). At the same time, PI has strong water absorption, which will further damage its dielectric properties. In addition, the thermal expansion coefficient of PI (CTE ≥ 70ppm / K) is higher than that of copper foil (CTE = 22ppm / K), which leads to the PI layer in the copper clad laminate being prone to wrinkling, fracture, delamination, etc. in an environment of alternating hot and cold use. Even modified polyimide (MPI) flexible copper clad laminate (MPI-FCCL) cannot completely overcome these problems, so it performs insufficiently in 5G communication applications.
[0004] Liquid crystal polymer (LCP) has high heat resistance, low water absorption, low dielectric loss and high dimensional stability. In recent years, it has received widespread attention in high-frequency circuit substrates or circuits for high-speed transmission lines, and is considered to be an ideal material for 5G high-frequency signal transmission. Compared with traditional PI film, LCP has many advantages as a copper clad laminate substrate. First, LCP has excellent dielectric properties, and its dielectric constant and dielectric loss are low, which makes LCP-FCCL have lower signal loss during high-frequency signal transmission, and is particularly suitable for high-frequency application scenarios such as 5G communication. Secondly, LCP exhibits excellent thermal stability and dimensional stability, and has a small thermal expansion coefficient, which helps to improve the reliability of electronic products. In addition, LCP also has excellent chemical resistance and moisture resistance, and can maintain stable performance in harsh environments. Finally, LCP has a low density, which helps to achieve lightweight design of electronic products. These advantages make LCP-FCCL have broad application prospects in high-end electronic products.
[0005] At present, there are two main ways to prepare LCP-FCCL: the first is to use a coating method to directly coat the LCP resin on the copper foil; the second is to make the LCP resin into a film and then attach it to the copper foil by pressing. As one of the main methods for producing LCP-FCCL, the coating method has some significant technical limitations. First, it is difficult to ensure the uniformity of the coating during the coating process, which may lead to uneven thickness of the LCP layer and affect the electrical properties and mechanical strength of the product. In addition, the parameters of the coating process (such as coating speed, temperature, drying time, etc.) need to be precisely controlled, which not only increases the complexity of the production process, but also may affect the yield rate of the product. The advantage of the pressing method is that the thickness of the film can be precisely controlled, and the bonding of LCP and copper foil can be optimized by adjusting the temperature and pressure of the pressing. However, there are certain differences in the interfacial adhesion between LCP and copper foil, and improving the bonding between the two is an important research topic.
[0006] The traditional way to improve the copper clad bonding strength is generally to roughen the metal layer, that is, to increase the surface roughness of the copper foil, and enhance the bonding strength between the polymer substrate and the copper foil through the anchoring effect. However, this will lead to poor uniformity of the peel strength within the copper clad board surface, and it is easy to produce a skin effect, which will weaken the high-frequency performance of the liquid crystal polymer film.
[0007] In addition, there is another method of surface treating the liquid crystal polymer film. For example, patent US20140023881A1 discloses a method for manufacturing a copper-clad laminate of a liquid crystal polymer film, which uses plasma to treat the surface of the liquid crystal polymer film, and then makes the treated liquid crystal polymer film into a copper-clad laminate. Patent CN111901977A discloses a method for preparing a copper-clad laminate of a liquid crystal polymer film, which performs plasma activation treatment on the liquid crystal polymer film, deposits copper on the surface of the treated film, and then continuously plates copper on the resulting copper layer to obtain a copper-clad laminate of a liquid crystal polymer film. The disadvantage of this method is that the surface treatment is usually time-sensitive, and the treated liquid crystal polymer film must be immediately copper-clad, otherwise the activation effect will decay or even fail. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a modified liquid crystal polymer composition, a copper clad laminate and a preparation method thereof. By adding a modifying additive to the liquid crystal polymer resin, the wettability between the modified liquid crystal polymer film and the copper foil is improved, the bonding force between the modified liquid crystal polymer film and the copper foil is enhanced, and the copper clad laminate has excellent peel strength.
[0009] The present invention provides the following technical solutions: In a first aspect, a modified liquid crystal polymer composition is provided, comprising a liquid crystal polymer resin, a modified additive, a lubricant and / or an antioxidant; The mass ratio of the liquid crystal polymer resin to the modified additive is (80-99):(1-20); The modified additive is selected from one or more combinations of polyolefin elastomer (POE), tackifying resin, ethylene-vinyl acetate copolymer (EVA), and polyethylene succinate (PES) copolyester.
[0010] Furthermore, the modified liquid crystal polymer composition comprises the following components in parts by weight: 90-99 parts of liquid crystal polymer resin, 1-10 parts of modified additive, 0.1-1 parts of lubricant, and 0.01-0.5 parts of antioxidant.
[0011] Furthermore, the liquid crystal polymer resin is selected from film-grade resins having a melting point greater than or equal to 280°C.
[0012] Furthermore, the lubricant is selected from a combination of one or more of stearic acid lubricants, stearyl alcohol lubricants, and stearate lubricants. The addition of lubricants can improve the internal friction heat generation of the liquid crystal polymer resin melt and the fluidity of the modified additive melt, and reduce thermal degradation.
[0013] Furthermore, the lubricant is selected from a combination of one or more of magnesium stearate, zinc stearate, glyceryl monostearate, and pentaerythritol stearate.
[0014] Furthermore, the lubricant is preferably stearic acid monoglyceride.
[0015] Furthermore, the antioxidant is selected from a combination of one or more of antioxidant 168, antioxidant 246, and antioxidant 1010.
[0016] Furthermore, the antioxidant is preferably a compound of antioxidant 168 and antioxidant 1010.
[0017] In a second aspect, a method for preparing a copper clad laminate is provided, comprising the following steps: The components of the modified liquid crystal polymer composition of the first aspect are placed in a mixer according to a proportion and mixed, and the mixed raw materials are put into a twin-screw extruder, and the modified liquid crystal polymer composition is obtained by melting, blending, extruding and granulating; The modified liquid crystal polymer composition is put into a single screw extruder, and the modified liquid crystal polymer film is obtained by extrusion casting or extrusion film blowing; The modified liquid crystal polymer film is drawn to a pressure roller and compounded with copper foil to obtain a copper clad laminate.
[0018] Furthermore, the rotation speed of the twin-screw extruder is 200-500 rpm / min, and the temperature is Tm+10° C.-Tm+20° C., wherein Tm is the melting point of the liquid crystal polymer resin.
[0019] Furthermore, when the single screw extruder is used to extrude the blown film, the temperature is Tm+10°C ~Tm+20°C, the blowing ratio is (10:6)~(4:3), and the drawing ratio is (2:1)~(5:1).
[0020] Furthermore, when the modified liquid crystal polymer film is pulled to the pressure roller and combined with the copper foil, the pressure is 0.2-2MPa and the temperature is Tm+5°C-Tm+25°C.
[0021] In a third aspect, a copper clad laminate prepared by the method described in the second aspect is provided.
[0022] Compared with the prior art, the present invention has the following beneficial effects: The modified liquid crystal polymer composition provided by the present invention comprises a liquid crystal polymer resin, a modifying additive, a lubricant and / or an antioxidant. The liquid crystal polymer resin is modified by the modifying additive so that the prepared modified liquid crystal polymer composition has a lower viscosity and a higher creep compliance. After the modified liquid crystal polymer composition is made into a modified liquid crystal polymer film and pressed with a copper foil, the modified liquid crystal polymer film and the copper foil have good wettability and strong bonding force, so that the obtained flexible copper clad laminate has excellent peel strength. Furthermore, by adjusting the amount of the modifying additive within the specified range of the present invention (the mass ratio of the liquid crystal polymer resin to the modifying additive is (80-99):(1-20)), the peel strength can be adjusted to the required strength, while too little modifying additive has no obvious effect on improving the peel strength, and too much modifying additive will migrate to the surface of the modified liquid crystal polymer composition during the cooling and curing process, greatly reducing its surface tension and significantly reducing its peel strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Graphs showing complex viscosities of modified liquid crystal polymer compositions in the embodiments of the present invention and the comparative examples; Figure 2 1 is a creep compliance diagram of the modified liquid crystal polymer composition in the embodiments of the present invention and the comparative examples; Figure 3 This is a diagram of the flexible copper clad laminate test sample after the peel strength test in Example 1 of the present invention; Figure 4 This is a diagram of the flexible copper clad laminate test sample after the peel strength test in Example 2 of the present invention; Figure 5 This is a diagram of the flexible copper clad laminate test sample after the peel strength test in Example 4 of the present invention; Figure 6 This is a diagram of the flexible copper clad laminate test sample in Comparative Example 1 of the present invention after the peel strength test. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0025] The manufacturers and brand information of the raw materials used in the following examples are as follows: Liquid crystal polymer resin, manufactured by Japan Polyplastics, brand A950RX; Polyolefin elastomer, manufactured by ExxonMobil, brand POE-8880; Tackifying resin, manufactured by ExxonMobil, brand name Escorez-5637; Ethylene-vinyl acetate copolymer, manufactured by Unica Japan, brand name DQDJ-1868; Polyethylene succinate copolyester, manufactured by Shanghai Aladdin; Lubricant, glyceryl monostearate, manufactured by Shanghai Kaisai Chemical; Antioxidant, manufactured by Sinopharm Chemical Reagent Co., Ltd., brand numbers 168 and 1010.
[0026] Example 1
[0027] (1) Prepare the modified liquid crystal polymer composition according to the following components in parts by mass: 98 parts of liquid crystal polymer resin, 2 parts of polyolefin elastomer, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0028] (2) The raw materials of each component in step (1) are placed in an oven at 140° C. and baked for 5 h to remove moisture, and then the dried raw materials are placed in a high-speed mixer and mixed at high speed for 5 min; the mixed raw materials are then placed in a twin-screw extruder at a speed of 500 rpm / min and a temperature of 290-300° C., and melted, blended, extruded and granulated to obtain a modified liquid crystal polymer composition.
[0029] (3) The modified liquid crystal polymer composition is put into a single screw extruder, and a modified liquid crystal polymer film is obtained by extrusion and film blowing. In the film blowing process, the temperature is 290-300°C, the blowing ratio is 6:4, and the drawing ratio is 3:1. The thickness of the obtained modified liquid crystal polymer film is 50 μm.
[0030] (4) The modified liquid crystal polymer film is pulled onto a pressure roller and composited with a copper foil having a thickness of 50 μm, a composite temperature of 290°C, and a pressure of 1.0 MPa to form a flexible copper clad laminate.
[0031] Example 2
[0032] The difference between this embodiment and embodiment 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 95 parts of liquid crystal polymer resin, 5 parts of polyolefin elastomer, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0033] Example 3
[0034] The difference between this embodiment and embodiment 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 98 parts of liquid crystal polymer resin, 2 parts of tackifying resin, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0035] Example 4
[0036] The difference between this embodiment and embodiment 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 95 parts of liquid crystal polymer resin, 5 parts of tackifying resin, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0037] Example 5
[0038] The difference between this embodiment and embodiment 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 95 parts of liquid crystal polymer resin, 5 parts of ethylene-vinyl acetate copolymer, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0039] Example 6
[0040] The difference between this embodiment and embodiment 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 95 parts of liquid crystal polymer resin, 5 parts of polyethylene glycol succinate copolyester powder, 0.2 parts of glycerol monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0041] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (1), the modified liquid crystal polymer composition is prepared according to the following components in parts by weight: 100 parts of liquid crystal polymer resin, 0.2 parts of glyceryl monostearate, 0.1 parts of antioxidant 168, and 0.1 parts of antioxidant 1010.
[0042] Performance Testing (1) Melt flow rate test: The test was performed in accordance with GB / T 3682.2-2018. The modified liquid crystal polymer compositions prepared in Examples 1 to 6 and Comparative Example 1 were dried at 150°C for 5 h, and then placed on a melt flow rate tester. The test was performed after pre-melting at 290°C for 3 min, with a load of 2.16 kg. The test results are shown in Table 1.
[0043] Table 1 Melt flow rate test results of modified liquid crystal polymer compositions of Examples and Comparative Examples
[0044] (2) Complex viscosity test: The test was conducted in accordance with GB / T 33061. The modified liquid crystal polymer compositions prepared in Examples 1 to 6 and Comparative Example 1 were dried at 150°C for 5 h, and then placed on a rotational rheometer. After pre-melting at 295°C for 3 min, the complex viscosity was tested in the range of 50-0.01 Hz in the frequency sweep mode. The results are as follows: Figure 1 shown.
[0045] (3) Creep compliance test: The test was conducted in accordance with GB / T 33061. The modified liquid crystal polymer compositions prepared in Examples 1 to 6 and Comparative Example 1 were dried at 150°C for 5 h, and then placed on a rotational rheometer. After pre-melting at 295°C for 3 min, the creep compliance was tested in the creep mode with a test stress of 1 kPa and a test time of 5 min. The results are as follows: Figure 2 shown.
[0046] (4) Peel strength test: Tested in accordance with the test method of IPC-TM-6502.4.8. Use the flexible copper clad laminate prepared in Examples 1 to 6 and Comparative Example 1 to make a peel test sample with a width of 1 mm. At room temperature, peel off the bonding surface of the liquid crystal polymer film layer and the copper foil layer from the edge, fix the copper foil layer on the flat plate with double-sided tape, and peel off the liquid crystal polymer film layer in a 180° direction at a speed of 50 mm / min. Use a tensile testing machine to record the peel load. Take the sample with a peel length greater than 100 mm as the valid sample, and calculate the peel strength based on the average value of the load during the peeling process. The test results are shown in Table 2. The states of the test samples of Example 1, Example 2, Example 4 and Comparative Example 1 after the peel strength test are as follows: Figure 3 , Figure 4 , Figure 5 and Figure 6 shown.
[0047] Table 2 Peel strength test results of modified liquid crystal polymer films of the embodiments and comparative examples
[0048] like Figure 1As shown in Table 1, by comparing Examples 1 to 6 with Comparative Example 1, it can be seen that the technical solution provided by the present invention can effectively improve the melt index of the resin and reduce the viscosity of the resin by adding an appropriate amount of modifying additives to the liquid crystal polymer.
[0049] like Figure 2 As shown, from the comparison between Examples 1 to 6 and Comparative Example 1, it can be seen that the technical solution provided by the present invention can simultaneously improve the creep compliance of the resin by adding an appropriate amount of modifying additives to the liquid crystal polymer, thereby improving the wetting performance with the copper foil.
[0050] As shown in Table 2 and Figure 3~Figure 6 As shown, by comparing Examples 1 to 6 with Comparative Example 1, it can be seen that the technical solution provided by the present invention effectively improves the peel strength between the liquid crystal polymer film layer and the copper foil layer, that is, enhances the bonding force between the liquid crystal polymer film and the copper foil, so that the flexible copper clad laminate has excellent peel strength.
[0051] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified liquid crystal polymer composition, characterized in that: It includes liquid crystal polymer resin, modification additive, lubricant and / or antioxidant; The mass ratio of the liquid crystal polymer resin to the modified additive is (80-99):(1-20); The modifying additive is selected from one or more combinations of polyolefin elastomers, tackifying resins, ethylene-vinyl acetate copolymers, and polyethylene succinate copolyesters.
2. The modified liquid crystal polymer composition according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 90-99 parts of liquid crystal polymer resin, 1-10 parts of modified additive, 0.1-1 parts of lubricant and 0.01-0.5 parts of antioxidant.
3. The modified liquid crystal polymer composition according to claim 1, characterized in that: The liquid crystal polymer resin is selected from film-grade resins having a melting point greater than or equal to 280°C.
4. The modified liquid crystal polymer composition according to claim 1, characterized in that: The lubricant is selected from one or more combinations of stearic acid lubricants, stearyl alcohol lubricants, and stearate lubricants.
5. The modified liquid crystal polymer composition according to claim 1, characterized in that: The antioxidant is selected from a combination of one or more of antioxidant 168, antioxidant 246, and antioxidant 1010.
6. A method for preparing a copper clad laminate, characterized in that: The following steps are involved: The components of the modified liquid crystal polymer composition according to any one of claims 1 to 5 are mixed in a mixer according to a proportion, and the mixed raw materials are put into a twin-screw extruder, and the modified liquid crystal polymer composition is obtained by melting, blending, extruding and granulating; The modified liquid crystal polymer composition is put into a single screw extruder, and the modified liquid crystal polymer film is obtained by extrusion casting or extrusion film blowing; The modified liquid crystal polymer film is drawn to a pressure roller and compounded with copper foil to obtain a copper clad laminate.
7. The method for preparing a copper clad laminate according to claim 6, characterized in that: The rotation speed of the twin-screw extruder is 200-500 rpm / min, and the temperature is Tm+10° C.-Tm+20° C., wherein Tm is the melting point of the liquid crystal polymer resin.
8. The method for preparing a copper clad laminate according to claim 6, characterized in that: When a single screw extruder is used to extrude blown film, the temperature is Tm+10°C~Tm+20°C, the blowing ratio is (10:6)~(4:3), and the drawing ratio is (2:1)~(5:1).
9. The method for preparing a copper clad laminate according to claim 6, characterized in that: When the modified liquid crystal polymer film is pulled to the pressure roller and composited with the copper foil, the pressure is 0.2-2MPa and the temperature is Tm+5°C-Tm+25°C, wherein Tm is the melting point of the liquid crystal polymer resin.
10. A copper clad laminate prepared by the method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Preparation method of liquid crystal polymer flexible copper-clad plate
CN111901977A
Liquid Crystal Polymer Film Based Copper-Clad Laminate and Method for Producing Same
US20140023881A1
Low-cost thermoplastic polyolefin-based copper-clad plate
CN108437593A
Resin-clad metal foil and flexible printed wiring board
CN108702840A
Liquid crystal polymer flexible copper-clad plate and manufacturing method thereof
CN111605265A